Low prevalence of known pathogenic mutations in dominant PD genes: A Swedish multicenter study. (September 2019) - Puschmann, Andreas; Jiménez-Ferrer, Itzia; Lundblad-Andersson, Elin; Mårtensson, Emma; Hansson, Oskar; Odin, Per; Widner, Håkan; Brolin, Kajsa; Mzezewa, Ropafadzo; Kristensen, Jonas; Soller, Maria; Rödström, Emil Ygland; et al.
Abstract: Objective: To determine the frequency of mutations known to cause autosomal dominant Parkinson disease (PD) in a series with more than 10% of Sweden's estimated number of PD patients. Methods: The Swedish Parkinson Disease Genetics Network was formed as a national multicenter consortium of clinical researchers who together have access to DNA from a total of 2, 206 PD patients; 85.4% were from population-based studies. Samples were analyzed centrally for known pathogenic mutations in SNCA (duplications/triplications, p.Ala30Pro, p.Ala53Thr) and LRRK2 (p.Asn1437His, p.Arg1441His, p.Tyr1699Cys, p.Gly2019Ser, p.Ile2020Thr). We compared the frequency of these mutations in Swedish patients with published PD series and the gnomAD database. Results: A family history of PD in first- and/or second-degree relatives was reported by 21.6% of participants. Twelve patients (0.54%) carried LRRK2 p.(Gly2019Ser) mutations, one patient (0.045%) an SNCA duplication. The frequency of LRRK2 p.(Gly2019Ser) carriers was 0.11% in a matched Swedish control cohort and a similar 0.098% in total gnomAD, but there was a marked difference between ethnicities in gnomAD, with 42-fold higher frequency among Ashkenazi Jews than all others combined. Conclusions: In relative terms, the LRRK2 p.(Gly2019Ser) variant is the most frequent mutation among Swedish or international PD patients, and in gnomAD. SNCA duplications were the second most common of the mutations examined. In absolute terms, however, these known pathogenic variants in dominant PD genes are generally very rare and can only explain a minute fraction of familial aggregation of PD. Additional genetic and environmental mechanisms may explain the frequent co-occurrence of PD in close relatives. Graphical abstract: Image 1 Highlights: We screened 2206 PD patients from Sweden for 8 mutations known to cause dominant PD. SNCA copy number variants and seven point mutations in LRRK2 and SNCA were analyzed. Twelve patients (0.54%) carried LRRK2 p.(Gly2019Ser), and one an SNCA duplication. In GnomAD, 0.098% of individuals carry LRRK2 p.(Gly2019Ser). LRRK2 p.(Gly2019Ser) is 42-fold more frequent in Ashkenazi than all others.